Urolithiasis in guinea pig (Cavia Porcellus): Case Report - Sato Pimenta, Yara Tayna Sato Pimenta; Pimenta, Yara Tayna Sato; Segala, Renato Dalcin; Pita, Maria Carolina Gonçalves; Salzedas, Breno Aguiar; Lopes, Denise Macedo (Pubvet, 2019)
Urolithiasis is a common disease characterized by the presence of stones in any segment of the urinary tract that affects guinea pig. Usually the calculus or uroliths are located in the bladder and urethra, mostly calcium-based (Calcium Carbonate and Calcium Phosphate). Females, especially those older than 4 years, are more affected. The clinical signs vary according to the location and quantity these calculi get together. The diagnosis is made with ultrasonography and radiographic with additional examinations that are required to assist the prognosis. The treatment is by surgery, which may be done by cystoscopy in females as well as a support treatment, besides owner orientation about diets and management, focusing on reducing incidence relapse. This paper reports a guinea pig clinical case, female, 4.8 years old, attended at the Veterinary School Clinic of the Universidade de Guarulhos, clinically diagnosed as tumor formation without mobility on a perivulve region, which a urolith were removed of the region by urethrotomy during surgery.